Acknowledgement to Reviewers of Philosophies in 2019 - Philosophies Editorial Office (Philosophies, 2020)
The editorial team greatly appreciates the reviewers who have dedicated their considerable time and expertise to the journal’s rigorous editorial process over the past 12 months, regardless of whether the papers are finally published or not [...]